Effect of sepiolite organomodification on the performance of PCL/sepiolite nanocomposites. (December 2017) - Nikolic, Marija S.; Petrovic, Rada; Veljovic, Djordje; Cosovic, Vladan; Stankovic, Nadezda; Djonlagic, Jasna
Graphical abstract: Highlights: PCL/sepiolite nanocomposites were prepared by solution casting. Two types of organic modification/organic modificator of sepiolites were employed. Organomodified sepiolites show better compatibility with PCL matrix. Mechanical performance was improved with organomodified sepiolites. Abstract: Poly(ε-caprolactone) (PCL) based nanocomposites with unmodified and organomodified sepiolites were prepared by solution casting method. The sepiolites were modified with short (3-mercaptopropyl)trimethoxysilane (SEP-SI) by using covalent grafting or with long hexadecylamine (SEP-HDA) by using ionic exchange. In order to reveal the influence of the organomodification on the nanoclay dispersion and the properties of the nanocomposites XRD, DSC, TG, SEM, TEM, optical microscopy, melt rheology and dynamic-mechanical analyses were performed. A better dispersion was achieved when organomodified sepiolites instead of native ones were used as fillers. As deduced from the melt rheology data, by analysis of the Cole-Cole plots, the best dispersion was obtained for SEP-SI nanoclay. The thermal stability was not improved, however in the initial stages of the thermo-oxidative degradation a delay in the weight loss was observed for nanocomposites with organomodified sepiolites. The mechanical properties of the nanocomposites were improved in comparison to PCL, particularly for those with modified sepiolites. In terms of mechanical properties the use of sepiolite modified with HDA gave the best results, as a consequence of better interaction between longer alkyl hydrophobic part of the organic modificator and the hydrophobic PCL matrix.